2012
DOI: 10.2519/jospt.2012.3827
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural Adaptation and Measurement Properties of an Italian Version of the Western Ontario Shoulder Instability Index (WOSI)

Abstract: Shoulder instability can be defined as the inability to maintain the normal position of the humeral head on the glenoid during upperlimb movements, which causes apprehension and/or pain.11 Acute traumatic anterior dislocation is the most common cause of shoulder instability. Shoulder instability may not manifest during clinical examination. The symptoms are typically intermittent and variable, thus an accurate assessment of symptoms over time and life circumstances is required to accurately portray the functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
48
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 45 publications
19
48
1
Order By: Relevance
“…Because there are no domains in OISS, the internal consistency covers the total score of all 12 items. For WOSI findings are in keeping previous versions [37,38], but higher than those reported for the domain lifestyle [39,40]. For EQ-VAS, the Chronbach’s alpha was in keeping with the results of Adobor et al [41], slightly lower for EQ-5D.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Because there are no domains in OISS, the internal consistency covers the total score of all 12 items. For WOSI findings are in keeping previous versions [37,38], but higher than those reported for the domain lifestyle [39,40]. For EQ-VAS, the Chronbach’s alpha was in keeping with the results of Adobor et al [41], slightly lower for EQ-5D.…”
Section: Discussionsupporting
confidence: 85%
“…For the WOSI, it was in accordance with the original version and later published versions [2,37,38], and for EQ-VAS it was slightly higher than that of the original version [12]. In contrast to previous studies the reliability of EQ-5D was not acceptable in the present study [12,41].…”
Section: Discussionsupporting
confidence: 82%
“…Cacchio et al [15] reported an SEM of 71 and an SDC of 196 in 64 patients. We found much higher SEM and SDC values (174 and 483, respectively), indicating that a patient has to improve at least 23% of the total score (483/2100 possible points) to ensure an improvement beyond measurement error.…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed by Salomonsson et al, Hofstaetter et al, and Cacciho et al [11,12,15] all had smaller patient populations (32, 25, and 30, respectively) and differed in their treatment-free test–retest interval. Hoffsaetter et al and Cacchio et al used a test–retest interval of 24–72 h and 3 days or 14 weeks, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation